Evaluation of The Implementation of Scouting Extracurricular Activities - Diana; Fran Sisko; Wahyu Irawan, Puspita; Eni Astrianti Putri; Sulistiyono (Journal of Practice Learning and Educational Development, 2026)
This study aims to evaluate Scouting activities at SMA Negeri 13 Rejang Lebong to determine the implementation of Scouting activities that have been carried out and to see the effectiveness of Scouting activities in shaping student character, independence, and discipline. This study uses descriptive qualitative research with an evaluation type of research using the CIPP (Context, Input, Process, and Product) model. This study uses descriptive qualitative analysis with data collection using interview sheets, observation, and documentation. Context aspect: Scouting extracurricular activities at SMA Negeri 13 Rejang Lobong have a strong legal basis. Input aspect: the implementation of Scouting activities at SMA Negeri 13 Rejang Lobong has been supported by adequate facilities and infrastructure and competent coaches. However, there is still a shortage of female coaches. Process aspect: the implementation of Scouting activities at SMA Negeri 13 Rejang Lobong has a good planning system and is carried out in a structured manner. Product Aspect: The implementation of Scouting extracurricular activities at SMA Negeri 13 Rejang Lebong has had a significant positive impact on students. Therefore, it can be concluded that Scouting extracurricular activities at SMA Negeri 13 Rejang Lebong are running well and should be continued and improved.